Development of Lampung Culture-based Student Worksheets on Flat Shapes Materials - Hariz Arifai; Suherman Suherman; Rosida Rakhmawati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2021)
This research aimed to develop the Lampung culture-based student worksheet to produce viable, interesting and effective media. This study uses a research development method with the steps: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The subjects in this study were students of SMP PGRI 6 Bandar Lampung with data collection instruments used in the form of a questionnaire given to material experts, media experts, attractiveness tests and effectiveness tests on Lampung Culture-based student worksheet that were developed. This research resulted in: 1) Lampung culture-based students worksheet, there is a flat-build material with a very decent criterion with a score of 3.50 based on the assessment of material experts and 3.33 by experts. 2) The students' responses in Lampung culture-based students worksheet on flat-build material obtained a score of 3.52 with very interesting criteria in the small class test in class VII E and in the large class test a score of 3.43 in class VII G was interesting. 3) the students worksheet on flat shapes material was proven effective with an effect size score of 0.54 with medium criteria. To conclude, Lampung culture-based students worksheet on flat material can be used in the learning process.